Unveiling the Truth: Honey Bees’ Astonishing Adaptation to Human Management: Μέλι μέλισσα ανθρώπινη προσαρμογή - Ilyasov, RA; Boguslavsky, DV; Ilyasova, AY; Davydova, ED; Atnagulova, AA; Sattarov, VN; Khrapova, SN; Mannapov, AG; Kekeçoğlu, M (Journal of the Hellenic Veterinary Medical Society, 2025)
The honey bee, Apis mellifera L., originated on the supercontinent Gondwana over 100 million years ago. It evolved in Southeast Asia and diversified into subspecies in North Africa, eventually spreading to Western Asia and Northern Europe. This species remained largely unchanged until it encountered humans approximately 10,000 years ago, leading to significant alterations through domestication. Human-induced hybridization has since blurred the geographic boundaries of subspecies, posing threats to honey bee diversity and resulting in the loss of many subspecies that formed 100,000 years ago. Despite these challenges, local honey bee populations have demonstrated greater resistance to environmental factors compared to introduced lines, underscoring the importance of selecting subspecies and ecotypes adapted to local conditions. Genetic diversity is crucial for supporting honey bees’ evolutionary potential and their ability to adapt to changing environments. Understanding the historical relationship between humans and honey bees is essential for developing strategies that enhance their ecological adaptation and foster mutually beneficial relationships. Although honey bees may appear independent, modern humans and honey bees have become interdependent partners, enhancing their adaptation, resilience, and survival through cooperation. This mutual relationship highlights the importance of conserving the biological and genetic diversity of honey bees, ensuring their continued benefits to agriculture and the environment. Based on our experiences, we contend that modern beekeeping is not rooted in domestication but rather in the management of semi-wild bees.